An Innovative, Experiential-Learning Project for Sales Management and Professional Selling Students. Issue 1 (2nd January 2016) - Chapman, Joseph; Schetzsle, Stacey; Wahlers, Russell
Abstract : This article presents an innovative, experiential-learning project that incorporates students from two different courses: sales management and professional selling. Sales management students actually manage sales students on an outside sales project. Students apply classroom knowledge to a real-life sales project for a local community organization. The sales project discussed in this article is a fundraising project for Big Brothers Big Sisters.